Effect of cover crops and tillage systems on soil quality and sugarcane yield - Carneiro, Marina Pedroso; de Souza, Zigomar Menezes; Farhate, Camila Viana Vieira [UNESP]; Cherubin, Maurício Roberto; Panosso, Alan Rodrigo [UNESP] (Wiley, 2024)
The management adopted in the establishment and replanting of sugarcane fields, with conventional tillage followed by fallow, is one of the main causes of soil quality degradation. In this context, the soil quality index (SQI) is an important tool to guide the use of more sustainable practices and management. This study aimed to monitor the effect of different cover crops in association with different tillage systems on sugarcane yield based on key indicators and an SQI developed using the Soil Management Assessment Framework (SMAF). The experiment was carried out on a sugarcane expansion area located in the municipality of Ibitinga, São Paulo, Brazil. The following soil physical and chemical attributes were analyzed: soil bulk density, macroaggregates, available phosphorus and potassium. Soil carbon content was also analyzed and used to calculate the SQI. Productivity over the 4 years of sugarcane cultivation was also analyzed. The use of subsoilers for soil tillage proved efficient in managing compaction by providing lower soil bulk density values in the first years of cultivation (1.59 and 1.63 g cm−3); however, these effects occurred in the short term with a 10% increase in later years. The use of millet in association with subsoiling showed the best results for soil quality (0.59), reflected in the maintenance of yields at 100 Mg ha−1 over time. Thus, our study reinforces the importance of using soil conservation systems in sugarcane replanting areas to achieve production longevity.
Keywords: cover crops; millet; no-tillage; subsoiler; sunn hemp; tillage